An exploration of problems experienced in the interpretation of word problems by grade 12 learners - Neshuku, Christian N (Rhodes University, Faculty of Education, Department of Education, 2009)
This research sought to investigate the problems experienced in the interpretation of word problems by senior secondary school learners, in particular to see how the language used in the articulation of word problems affects the interpretation. The study was conducted in a school in the Oshikoto region of Namibia, a school located in a semi-rural area of Namibia, and selected owing to the accessibility of the required participants. The research was located within an interpretive paradigm focusing on a study sample of 40 learners from a specified class in the selected school. Data were collected through written tests and a semi-structured interview based on written tests, and a comprehensive descriptive analysis of test results was prepared. The findings of the study indicate that the language in which the word problem was articulated did not make a difference. The performance in both English and Oshindonga tests was almost the same. The findings also indicate that vocabulary, syntactic interpretation, semantic relationships, algebraic skills, and practical sense making in relation to real-life are all important for the successful interpretation and solving of word problems. In view of these findings, the study has provided valuable insights into aspects of the teacher education curriculum that need to be revisited in order to improve the training of teachers In teaching word problems.
Keywords: Education (Secondary) -- Namibia; Word problems (Mathematics) Teachers -- Training of -- Namibia; Curriculum planning -- Namibia; Mathematics -- Study and teaching (Secondary)